2017
DOI: 10.31219/osf.io/k9tfa
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The interaction of contextual and syntactic information in the processing of Turkish anaphors

Abstract: In contrast with languages where anaphors can be classified into pronouns and reflexives, Turkish has a tripartite system that consists of the anaphors "o", "kendi", and "kendisi". The syntactic literature on these anaphors has proposed that whereas "o" behaves like a pronoun and "kendi" behaves like a reflexive, "kendisi" has a more flexible behavior and it can function as both a pronoun and a reflexive. Using acceptability judgments and a self-paced reading task, we examined how Turkish anaphors are processe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Further, they showed a complementary profile with reflexives, by dispreferring extra-sentential antecedents and preferring local and longdistance antecedents for kendisi and, to a lower extent, kendi as well. This finding is consistent with previous findings with Turkish monolinguals, which showed that kendi and kendisi both admit local and long-distance antecedents (Gračanin-Yuksek et al, 2017;Özbek and Kahraman, 2016). However, in contrast with the study by Gračanin-Yuksek and colleagues (2017), heritage speakers were also more likely to select long-distance antecedents with kendisi than with kendi, showing some distinction between these anaphors.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Further, they showed a complementary profile with reflexives, by dispreferring extra-sentential antecedents and preferring local and longdistance antecedents for kendisi and, to a lower extent, kendi as well. This finding is consistent with previous findings with Turkish monolinguals, which showed that kendi and kendisi both admit local and long-distance antecedents (Gračanin-Yuksek et al, 2017;Özbek and Kahraman, 2016). However, in contrast with the study by Gračanin-Yuksek and colleagues (2017), heritage speakers were also more likely to select long-distance antecedents with kendisi than with kendi, showing some distinction between these anaphors.…”
Section: Discussionsupporting
confidence: 93%
“…We followed the same data cleaning procedures as Gračanin-Yuksek et al (2017). Only participants with more than 70% accuracy in the filler trials were entered into the analysis (Lago et al, 2015;Parker et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations